STRATEGI PEMASARAN MELALUI INTERNET UNTUK MENINGKATKAN JUMLAH PENGUNJUNG DI DESA WISATA PENTINGSARI - , RAHAJENG SETYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of information technology is developing so fast. Humans use technology to improve their ability to work. Pentingsari tourism village is one of the tourist village in Sleman district, located below the slopes of the volcano Merapi is located exactly in the villages Umbulharjo, Cangkringan, Sleman Yogyakarta. In the tourist village Pentingsari still using conventional marketing to market attractiveness owned by Pentingsari tourist village, but there are more effective and efficient way to market rural tourism attraction Pentingsari using the internet. Constraints faced by tourists outside the area to be able to see the attractions and uniqueness Pentingsari tourist village is the distance between the locations where tourists stay with Pentingsari tourist village location and the lack of media appropriate information to be able to see all the info about tourist village Pentingsari. With the internet marketing is through facebook, twitter and website can help the tourists outside the area to be able to see the information directly Pentingsari tourist village, with marketing through the internet is also the number of visitors in the tourist village Pentingsari increased by 7%.